Spatial Assessment of Special Economic Zone Development for Decision Making: Case Study of Nong Khai Province - SRISAWAT, Anuwat; WIROJANAGUD, Wanpen (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2020)
This paper presents spatial assessment for special economic zone (SEZ) development at Nong Khai Province. Assessment employed spatial planning with Geographical Information System (GIS) based Multi Criteria Analysis (MCA). Methodology included 3 main parts. I. Preparation of data input to GIS; reviewing 11 proposed SEZ sites based on the public land covering the area exceeding 16 ha, setting the criterion or indicators for potential SEZ sites, weighting such indicators by MCA to create weight score. Indicators included size of area, condition of area use, plan for future development, land cost of surrounding area, impact to community, and impact to forest ecosystem. II. Assessment of potential sites; field survey of 11 proposed SEZ sites, impact level evaluation of each indicator, impact score evaluation by multiplying weight score and impact level. Impact scores of indicators and the proposed SEZ sites were processed through GIS. Three potential SEZ sites were outcome located in the lowest negative impact Sub-district. III. Assessment of suitable SEZ site; overlaying 3 SEZ potential sites on town planning map, only one SEZ site was classified as suitable SEZ site, which was Koke Soke Dindang Public Land at Sra Kai Sub-district, Sra Kai District, covering total area of 112 ha.